2021
DOI: 10.3389/fphar.2021.681525
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and Pro-apoptotic Effects of 18beta-Glycyrrhetinic Acid In Vitro and In Vivo Models of Rheumatoid Arthritis

Abstract: 18β-Glycyrrhetinic acid (18β-GA), an active component from Glycyrrhiza glabra L. root (licorice), has been demonstrated to be able to protect against inflammatory response and reduce methotrexate (MTX)-derived toxicity. This study was therefore designed to test the therapeutic possibility of 18β-GA on rheumatoid arthritis (RA) and to explore the underlying mechanism. LPS or TNF-α-induced inflammatory cell models and collagen-induced arthritis (CIA) animal models were applied in this study. Real-time quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…To induce an immune response, cells were stimulated with two pro-inflammatory factors—lipopolysaccharide (LPS) and tumor necrosis factor alpha (TNFα). LPS, isolated from the outer membrane of Escherichia coli, leads to strong pro-inflammatory stimulation, so it is often used to model the general immune response [ 19 , 20 , 21 , 22 ]. TNFα occurs naturally during the development of inflammation in the human body and is produced mainly by immune cells; thus, it invokes a more physiological FLS inflammatory response [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…To induce an immune response, cells were stimulated with two pro-inflammatory factors—lipopolysaccharide (LPS) and tumor necrosis factor alpha (TNFα). LPS, isolated from the outer membrane of Escherichia coli, leads to strong pro-inflammatory stimulation, so it is often used to model the general immune response [ 19 , 20 , 21 , 22 ]. TNFα occurs naturally during the development of inflammation in the human body and is produced mainly by immune cells; thus, it invokes a more physiological FLS inflammatory response [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar mechanisms were reported by Zhou et al [ 166 ] in LPS-induced inflammation murine macrophage RAW 264.7 cells; the results showed that the anti-inflammatory activity of GA occurs through the inhibition of NF-κB expression and attenuation of its nuclear translocation. Furthermore, the inhibition of the MAPK/NF-κB signaling pathway by GA was once again demonstrated by an in vitro and in vivo study as the main mechanism of GA anti-inflammatory action in rheumatoid arthritis [ 167 ].…”
Section: Glycyrrhetinic Acidmentioning
confidence: 99%
“…Enoxolone, glycyrrhetin, 3β-hydroxy-11oxo-18β, 20β-olean12-en-29oic acid, uralenic acid, or sub-glycyrrhelinic acid are all names for 18β-glycyrrhetinic acid. 18β-glycyrrhetinic acid have been described to reduce airway inflammation [ 16 , 17 ], alpha-naphthylisothiocyanate-induced cholestasis [ 18 ], D-GalN/LPS-induced acute liver injury [ 19 ], cyclophosphamide-induced hepatotoxicity [ 20 ], prostate tumor [ 21 ], lung cancer [ 22 ], gastric tumor [ 23 ], streptozotocin-induced diabetes [ 24 ], pulmonary arterial hypertension [ 25 ], visceral leishmaniasis [ 26 ], rotavirus replication [ 27 ], bacterial load [ 28 , 29 ], antipsychotic-induced hyperprolactinemia [ 30 ], myocardial infarction [ 31 ], hyperoxia exposure effects in neonatal rats [ 32 ], rheumatoid arthritis [ 33 ], fructose-induced nephropathy [ 34 ], radiation-induced skin damage [ 35 ], cisplatin-induced oxidative intestinal damage [ 36 ].…”
Section: Introductionmentioning
confidence: 99%